Body Structure Perception in Infancy. (21st October 2014) - Zieber, Nicole; Kangas, Ashley; Hock, Alyson; Bhatt, Ramesh S.
<x xml:space="preserve">Abstract</x> Structural cues, such as the relative size and arrangement of parts, are key aspects of adults' representation of human bodies, and they are used to derive significant social information such as age, sex, and attractiveness. Prior studies have not clearly addressed young infants' sensitivity to these body characteristics. In the current experiments, 3.5‐month‐olds exhibited a preference between images of intact bodies versus those with parts in wrong locations. Infants also discriminated between intact bodies and those with distorted part proportions. In both cases, infants discriminated when images were presented upright but not when they were inverted. These results indicate that infants are sensitive to the arrangement and size of human body parts at least by 3.5 months of age. Thus, contrary to some prior reports, body representation early in life is developed enough to include structural information.